Pelanggaran Prinsip Kerja Sama dalam Konten Terkonfirmasi Hoaks pada Situs Web Komdigi (Violations of the Cooperative Principle in Hoax Content Verified by the Ministry of Communication and Digital Affairs (Komdigi)) - Dini Febriani; Dhesti Qorita Ayun; Puteri Syanti Dewi Islami; Sumarlam Sumarlam (Universitas Sebelas Maret, 2026)
This study examines violations of Grice’s Cooperative Principle in three pieces of content confirmed as hoaxes on the Komdigi website in its May 8, 2026, edition. The study employs a qualitative method with a pragmatic approach. Data collection was conducted through observation and note-taking techniques on the transcriptions of the three hoax content pieces, while data analysis involved identifying and classifying violations of the four maxims of the Cooperative Principles. The results of the study found a total of 16 violations spread across the four maxims: the maxim of quantity was the most frequently violated with six violations, followed by the maxim of quality with four violations, and the maxims of relevance and manner with three violations each. The hoax content regarding foreign ship tariffs in the Malacca Strait recorded the most violations with seven, followed by the TB vaccine hoax with five violations, and the Donald Trump video hoax with four violations. This study concludes that violations of the principle of cooperation in hoax content constitute a deliberate linguistic strategy to manipulate information, exploit the audience’s emotions, and sway public opinion without support from verifiable facts.Penelitian ini mengkaji pelanggaran prinsip kerja sama Grice dalam tiga konten yang telah terkonfirmasi hoaks pada situs web Komdigi edisi 8 Mei 2026. Penelitian menggunakan metode kualitatif dengan pendekatan pragmatik. Pengumpulan data dilakukan melalui metode simak dan teknik catat terhadap transkripsi teks ketiga konten hoaks, sedangkan analisis data dilakukan dengan mengidentifikasi dan mengklasifikasikan pelanggaran keempat maksim prinsip kerja sama. Hasil penelitian menemukan total 16 pelanggaran yang tersebar pada empat maksim, maksim kuantitas menjadi yang paling banyak dilanggar dengan enam pelanggaran, diikuti maksim kualitas dengan empat pelanggaran, serta maksim relevansi dan maksim cara masing-masing tiga pelanggaran. Konten hoaks tarif kapal asing di Selat Malaka mencatatkan pelanggaran terbanyak dengan tujuh pelanggaran, disusul hoaks vaksin TBC dengan lima pelanggaran, dan hoaks video Donald Trump dengan empat pelanggaran. Penelitian ini menyimpulkan bahwa pelanggaran prinsip kerja sama dalam konten hoaks merupakan strategi kebahasaan yang disengaja untuk memanipulasi informasi, mengeksploitasi emosi audiens, serta menggiring opini publik tanpa dukungan fakta yang dapat diverifikasi.